2018
DOI: 10.1016/j.chemosphere.2018.06.110
|View full text |Cite
|
Sign up to set email alerts
|

Application of field-portable-XRF for the determination of trace elements in deciduous leaves from a mine-impacted region

Abstract: Deciduous leaves (n = 87) from beech (Fagus sylvatica), birch (Betula spp.) and oak (Quercus spp.) trees have been collected from three metal mine-impacted sites in southwest England and tested for concentrations of trace elements (As, Cu, Pb and Zn) using a field-portable-x-ray fluorescence (FP-XRF) spectrometer configured in a low density mode and housed in a stand. When intact leaves were analysed directly, mean detection limits ranged from about 10 (As) to 70 μg g (Cu) on a fresh weight basis; after freeze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…For example, traces of elemental ions can be measured using X-ray fluorescence as tested by Turner et al . 39 . They measured traces of As, Cu, Pb and Zn on leaf surfaces using a field portable x-ray fluorescence equipment (FP-XRF).…”
Section: Discussionmentioning
confidence: 99%
“…For example, traces of elemental ions can be measured using X-ray fluorescence as tested by Turner et al . 39 . They measured traces of As, Cu, Pb and Zn on leaf surfaces using a field portable x-ray fluorescence equipment (FP-XRF).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of the present study, although preliminary, point out the feasibility of an investigation that would permit obtaining information on the health status of urban populations, combining high spatial density and low cost. Furthermore, recent investigations on other types of bioindicators have shown that there are measurements able to provide information on atmospheric metal pollution by means of other analytical techniques, even simpler and cheaper than atomic emission spectrometry, such as X-ray fluorescence [42][43][44] and magnetic analysis [45][46][47][48][49]. This would make the approach accessible to a large number of laboratories in terms of purchase and operating costs of equipment.…”
Section: Resultsmentioning
confidence: 99%
“…The use of pXRF for in situ measuring in the field is increasing and as is evidence of the tool's reliability, most notably Radu and Diamond [24], Bull, Brown and Turner [38], Turner and Solman [39], Rincheval, Cohen and Hemmings [28], Turner et al [29,40] and Lemière et al [41]. Researchers analyzed many forms of media, including algae, bark, soil and sediments, and all demonstrate that the results produced by the pXRF were as reliable as those produced in laboratory, using methods, such as ICP-MS. Based on the comparative analyses presented in [27][28][29][38][39][40][41], we argue that in situ measurements with the pXRF are valid as a quick-scan method for mapping PTE pollutants in SuDS. Radu and Diamond [27] have conducted an extensive study correlating pXRF results with results from laboratory atomic absorption spectrophotometry (AAS), giving pXRF credential as a predictable in situ measuring tool.…”
Section: Results Almelomentioning
confidence: 99%